Catalytic pyrolysis of lignin over ZSM-5, alkali, and metal modified ZSM-5 at different temperatures to produce hydrocarbons. (April 2022) - Nishu; Li, Yingkai; Liu, Ronghou
Abstract: Temperature and catalyst type greatly influence the chemical processes as well as the quality of the pyrolysis products. Catalytic fast pyrolysis (CFP) of lignin isolated from rice straw using three different catalysts was performed at different pyrolysis temperatures (450, 500, 550, and 600 °C) using pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS) to explore the suitable catalytic performance for hydrocarbon production. The shape selectivity and acidity of the three catalysts (ZSM-5, NaOH-modified ZSM-5 (0.4 M), and nickel modified ZSM-5 (8 wt.%)), showed a substantial effect on the product distribution during CFP of lignin. Ni-ZSM-5 (8 wt.%) demonstrated effective performance for the transformation of oxygenated compounds through demethoxylation and dehydroxylation into aromatics. The most suitable pyrolysis temperature for catalytic pyrolysis of lignin was 550 °C in which a maximum selectivity of 72% for hydrocarbon was obtained over Ni-ZSM-5 (8 wt.%) followed by ZSM-5 (0.4 M) and ZSM-5. This research provides a suitable pyrolysis temperature and catalyst for high hydrocarbon production from catalytic pyrolysis of lignin. Highlights: Extracted lignin of rice straw was pyrolyzed at different temperatures over alkali and metal modified ZSM-5. The highest selectivity of hydrocarbons was achieved at 550 °C for both non-catalytic and catalytic pyrolysis of lignin. Ni-ZSM-5 (8 wt. %) showed maximum selectivity for hydrocarbon of 72%.